Building reciprocal relationships through decolonial practices in academic research - Bunmi Isaiah Omodan (Cogent Social Sciences)
This theoretical paper explores the implementation of decolonial practices in academic research, with a specific focus on fostering reciprocal relationships between researchers and researched communities. It argues that conventional research methodologies often perpetuate colonial power dynamics by extracting knowledge instead of facilitating knowledge exchange. Lensing this argument through decolonial practices, this paper suggests a shift towards reciprocity, where knowledge co-creation becomes the foundation of the research process. It examines various decolonial tools and strategies that promote mutual learning and respect. Furthermore, the paper acknowledges the challenges of implementing these practices within the rigid structures of academic institutions. It advocates for structural reforms that facilitate ethical engagement and ensure that research outcomes benefit all stakeholders, particularly those from marginalised communities. Ultimately, this paper proposes that fostering reciprocal relationships through decolonial practices not only enhances the ethical integrity of research but also leads to more profound and impactful knowledge production. This exploration is essential for academics who seek to align their research practices with principles of justice and equality, thereby promoting a shift towards a more inclusive and ethical academic environment.